CD154: An Immunoinflammatory Mediator in Systemic Lupus Erythematosus and Rheumatoid Arthritis - Nada Alaaeddine; Ghada S. Hassan; Daniel Yacoub; Walid Mourad (Clinical and Developmental Immunology)
Systemic lupus erythematosus and rheumatoid arthritis are two major chronic inflammatory autoimmune diseases with significant prevalence rates among the population. Although the etiology of these diseases remains unresolved, several evidences support the key role of CD154/CD40 interactions in initiating and/or propagating these diseases. The discovery of new receptors (αIIbβ3, α5β1, and αMβ2) for CD154 has expanded our understanding about the precise role of this critical immune mediator in the physiopathology of chronic inflammatory autoimmune diseases in general, and in systemic lupus erythematosus and rheumatoid arthritis in particular. This paper presents an overview of the interaction of CD154 with its various receptors and outlines its role in the pathogenesis of systemic lupus erythematosus and rheumatoid arthritis. Moreover, the potential usefulness of various CD154-interfering agents in the treatment and prevention of these diseases is also discussed.